Warisan Kuliner Randang Baluik sebagai Potensi Ekonomi di Nagari Pagaruyung Kabupaten Tanah Datar - Najmi, Najmi; Naldi, Hendra; Afriani, Rini; Silva, Ray; Nasution, Annisa Annida; Abianza, Erza (Jurusan Sejarah FIS UNP, 2024)
Nagari Pagaruyung which is located in Tanah Datar Regency is famous for producing rendang, especially